2001
DOI: 10.1109/3.910458
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model for design criteria of passively Q-switched lasers

Abstract: A general and straightforward model was developed for the design of passively -switched lasers. With the secondthreshold criterion and using a numerically fitting procedure, the output pulse energy was expressed as an analytical function of the initial transmission of the saturable absorber and the reflectivity of the output coupler. An analytical expression for the optimal output reflectivity was also obtained for maximizing the output pulse energy of a passively -switched laser with a given initial transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 15 publications
(30 reference statements)
1
52
0
Order By: Relevance
“…The problem of passively Q-switched lasers with simultaneous mode-locking has been treated experimentally and theoretically in many references [1][2][3][4][5][6][8][9][10] with, and without the existence of the IFD. None of the mentioned references discusses the impact of the polarization process on the characteristics of the output laser pulse.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…The problem of passively Q-switched lasers with simultaneous mode-locking has been treated experimentally and theoretically in many references [1][2][3][4][5][6][8][9][10] with, and without the existence of the IFD. None of the mentioned references discusses the impact of the polarization process on the characteristics of the output laser pulse.…”
Section: +mentioning
confidence: 99%
“…By assuming that the excited state lifetime of the absorber is larger than the laser pulse width, the instantaneous population inversion density of the uniform--pumped gain medium, in each period of pulse build-up, can be written in the following reduced form [2,3,5,6,9]:…”
Section: Analyzing the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective laser-beam area in the Nd:LLF crystal and in the SA was in a ratio (A∕A s ) of about 2.8. These conditions facilitate the second threshold condition being easily satisfied [21]. Initial experiments indicated that the PQS operation of the Nd:LLF laser was relatively sensitive to the position of V 3 :YAG, and the PQS characteristics were recorded when the V 3 :YAG was placed 5 mm away from the OC.…”
mentioning
confidence: 97%
“…It can be found that the pulse width varies only slightly with P abs , and the 3% OC cavity provides narrower pulse width than that of 8% OC at identical P abs . Based on the analysis of coupled rate equations [21,22], the population inversion of the Nd:LLF depleted in a very short time, and the pulse width saturated; thus the pump power has little influence on the pulse width. The average pulse widths were roughly to be 120.1 ns with 3% OC and 129.7 ns with 8% OC.…”
mentioning
confidence: 99%